PROFIL KELUARGA SAKINAH MAWADDAH WARAHMAH DI LINGKUNGAN MASYARAKAT ANGKOLA SANGKUNUR KABUPATEN TAPANULI SELATAN - Ahmad Sainul (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
The family is an important primary group in society. The family is a group formed from the long-standing relationship of men and women to create and raise children. So the family in its pure form is a social unit consisting of husband and wife and immature children. This unit has certain characteristics that are the same everywhere in the community unit. The sakinah mawaddah warahmah family referred to here is a family that carries out the rights and obligations in the household.Regarding household obligations according to fiqh, it cannot be separated from material and immaterial obligations. This means that something that is visible can be seen and felt like a dowry and a living. And something that cannot be felt like educating his wife and children and getting along well.The obligations themselves vary according to fiqh, which are explained as follows: Obligations of dowry/dowry. Living. The obligation to have a good relationship with the wife. Give love and affection to the wife. While the wife's obligations to her husband or a husband's right over his wife are, among others: Obedient to her husband. Take care of yourself when your husband is not around and Protecting husband's property